A Bibliometric Analysis of Overall and Top 100 Most-Cited Studies About Robotic Surgery Versus Open Surgery. (April 2022) - Chu, Xiajing; Yan, Peijing; Zhang, Na; Feng, Lufang; Guo, Kangle; Lu, Cuncun; Lu, Tingting; Wang, Chengbin; Yang, Ke-hu
Background: In the last 30 years, significant progress in the field of surgery has been achieved with the advent of robotic surgery. In this study, we aimed to conduct a bibliometric analysis to identify the distribution and characteristics overall and of the top 100 most-cited studies about robotic surgery versus open surgery. Methods: A systematic search was conducted on March 26, 2021 using Web of Science Core Collection. Two reviewers independently screened documents, and the top 100 most-cited studies were identified. Excel 2019 and VOSviewer were used to collect the data, and visual information was obtained. Results: A total of 2306 documents were searched from the Web of Science Core Collection, and 1065 journals and 2913 institutes were extracted. A significant growth was observed in the last 15 years. The number of citations from the United States accounted for 33.31% of the total number of citations. There were nine American institutes and one Swedish institute in the top 10 institutes. Four journals in the field of urology or gynecology were present in the top 10 published journals. Few global communications between authors, institutes, and countries authors were observed. Conclusion: The lack of close cooperation among scientific research institutions may have affected the industrialization process of surgical robots. Some developing countries, including South America and Africa, should seize the development opportunity of robotic surgery to improve the level of domestic research on robotic surgery.